Structure-function relationship between soluble epoxide hydrolases structure and their tunnel network - Karolina Mitusińska; Piotr Wojsa; Maria Bzówka; Agata Raczyńska; Weronika Bagrowska; Aleksandra Samol; Patryk Kapica; Artur Góra (Computational and Structural Biotechnology Journal, 2022)
Enzymes with buried active sites maintain their catalytic function via a single tunnel or tunnel network. In this study we analyzed the functionality of soluble epoxide hydrolases (sEHs) tunnel network, by comparing the overall enzyme structure with the tunnel’s shape and size. sEHs were divided into three groups based on their structure and the tunnel usage. The obtained results were compared with known substrate preferences of the studied enzymes, as well as reported in our other work evolutionary analyses data. The tunnel network architecture corresponded well with the evolutionary lineage of the source organism and large differences between enzymes were observed from long fragments insertions. This strategy can be used during protein re-engineering process for large changes introduction, whereas tunnel modification can be applied for fine-tuning of enzyme.